GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 4678 species occurrences available in GBIF matching the query: TaxonKey: Ipomoea nil (L.) Roth. The dataset includes 4678 records from 193 constituent datasets: 3 records from Guadeloupe_Herbier. 2 records from JOI - Herbário Joinvillea. 650 records from A global database for the distributions of crop wild relatives. 4 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1 records from HUEM - Herbário da Universidade Estadual de Maringá. 2 records from HUFU - Herbarium Uberlandense. 10 records from Phanerogamic Botanical Collections (S). 5 records from Census of the flora of Benin. 3 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 9 records from IAC - Herbário do Instituto Agronômico de Campinas. 2 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 290 records from Naturalis Biodiversity Center (NL) - Botany. 3 records from SPSF - Herbário Dom Bento José Pickel. 3 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 3 records from PRECIS. 25 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 5 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 1 records from SPF - Herbário da Universidade de São Paulo. 14 records from UFP - Herbário UFP - Geraldo Mariz. 1 records from HERBAM - Herbário da Amazônia Meridional. 32 records from ICN - Herbário do Instituto de Ciências Naturais. 75 records from Some Plant Specimens from KUN, IBSC, NAS Herbarium in China from 1900 to 1950. 11 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 4 records from The digitization of plant specimens of NTU. 46 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 1 records from Colección Herbario Universidad Católica de Oriente. 6 records from Museu Paraense Emilio Goeldi Herbarium. 3 records from CESJ - Herbário Leopoldo Krieger. 94 records from Plantae of Costa Rica (INBio). 20 records from Herbier du Bénin. 32 records from MBM - Herbário do Museu Botânico Municipal. 2 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Digital Florula - Las Cruces Biological Station. 51 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 4 records from FCAB - Herbário Friburguense. 320 records from Australia's Virtual Herbarium. 2 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 1 records from Natural History Museum Maastricht (NL) - Herbarium. 8 records from Consortium of California Herbaria. 2 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 8 records from iNaturalist Research-grade Observations. 1 records from UCBG TAPIR Provider. 72 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 13 records from ALCB - Herbário Alexandre Leal Costa. 1 records from HUSC - Herbário Unisanta. 1 records from HPBR - Herbário Padre Balduino Rambo. 60 records from NMNH occurrence DwC-A. 13 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 1 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 1 records from naturgucker. 137 records from Flora Atlas N.T.. 65 records from INPN - Données flore des CBN agrégées par la FCBN. 2 records from EFC - Herbário Escola de Florestas Curitiba. 21 records from ASE - Herbário da Universidade Federal de Sergipe. 12 records from UEC - Herbário da Universidade Estadual de Campinas. 12 records from FUEL - Herbário da Universidade Estadual de Londrina. 7 records from ICN - Universidad Nacional de Colombia. 59 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 12 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 8 records from Herbario del CIBNOR. 3 records from Vascular plant specimens of Akita Prefectural Museum. 1 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 5 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 421 records from Tropicos Specimen Data. 11 records from Natural History Museum (London) Collection Specimens. 2 records from Natural History Museum, Vienna - Herbarium W. 22 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 1 records from Inventario florístico de la Frailescana (zona focal), Chiapas, México. 1 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 4 records from Lista florística preliminar de Tamaulipas. 6 records from Base de datos de las regiones prioritarias 113 y 120 en los municipios de Zirándaro y Coahuayutla, (Guerrero). 1 records from Flora del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 14 records from Composición florística del Parque Nacional Huatulco. 2 records from Diversidad y riqueza vegetal de los substratos rocosos del centro del estado de Veracruz. 2 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 2 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 9 records from Formación del banco de datos del herbario (UCAM). 19 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 6 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 4 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 2 records from Botanical specimens database of Mr. Jiro Ito collection, Shizuoka Prefecture Museum of Natural History. 2 records from Ibaraki Nature Museum, Vascular Plants collection. 60 records from NMNH Extant Specimen and Observation Records. 1 records from Korean Ethnobotany Database. 114 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 1 records from Herbario UNAP. 8 records from The AAU Herbarium Database. 17 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 52 records from herbario. 31 records from Plant Specimens of Kurashiki Museum of Natural History. 4 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 3 records from Herbarium of Kitakyushu Museum of Natural History and Human History. 1 records from MEXU/Plantas Vasculares. 4 records from Plants of Papua New Guinea. 12 records from Herbarium Berolinense. 14 records from United States National Plant Germplasm System Collection. 43 records from The System-wide Information Network for Genetic Resources (SINGER). 6 records from Herbarium de Geo. B. Hinton, México. 13 records from Vascular Plants Collection of Sagamihara City Museum. 5 records from EURISCO, The European Genetic Resources Search Catalogue. 6 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 4 records from CVRD - Herbário da Reserva Natural Vale. 3 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 3 records from Kochi Prefectural Makino Botanical Garden. 1 records from MAR - Herbário do Maranhão. 14 records from Árboles de la Península de Yucatán, Flora del Distrito de Tehuantepec, Oaxaca y Familia Asteraceae en México (IBUNAM). 1 records from USF Herbarium. 32 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 2 records from HPAN - Herbário do Pantanal "Vali Joana Pott". 1 records from Herbier Ecole de Faune. 2 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 6 records from Field Museum of Natural History (Botany) Seed Plant Collection. 2 records from MBML-Herbario - Herbário Mello Leitão. 1 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 1 records from MISS_DC_01MAR2006. 1 records from R. L. McGregor Herbarium Vascular Plants Collection. 39 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 1 records from Gunma Museum of Natural History, Vascular Plant Specimen. 50 records from Plant. 4 records from Herbarium Senckenbergianum (FR). 43 records from SINGER Coordinator. 1 records from MEXU/Flora de Oaxaca. 2 records from Database of Native Plants in Taiwan. 7 records from University of Ghana - Ghana Herbarium. 2 records from Plant of Folklore (KIDR-PL). 9 records from Herbarium of Taiwan Forestry Research Institute. 1 records from Precis Plant Data. 2 records from WII Herbarium Dataset. 9 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 3 records from UPCB - Herbário do Departamento de Botânica. 17 records from Lund Botanical Museum (LD). 5 records from Census of the species of medicinal plant of Benin. Data mobilized in the framework of BID-AF2015-0065-NAC project and funded by EU. 7 records from Geographically tagged INSDC sequences. 2 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 1 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 12 records from TEPB - Herbário Graziela Barroso. 4 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 7 records from HTSA - Herbário do Trópico Semiárido. 1 records from Herbarium togoense. 15 records from HVASF - Herbário Vale do São Francisco. 19 records from HST - Herbário Sérgio Tavares. 1 records from Colección de Herbario. 39 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 358 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2 records from Bernice P. Bishop Museum. 2 records from FURB - Herbário Dr. Roberto Miguel Klein. 1 records from CRI - Herbário Pe. Dr. Raulino Reitz. 1 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 7 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 1 records from Seed collection – Dead seeds for evaluation and observation purposes. 124 records from Royal Botanic Garden Edinburgh Herbarium (E). 6 records from Botany (UPS). 68 records from Instituto de Ciencias Naturales. 1 records from CNMT - Herbário Centro Norte Mato Grossense. 29 records from UFPB - Herbário Lauro Pires Xavier - (JPB). 25 records from EAC - Herbário Prisco Bezerra. 18 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 2 records from Herbario de la Universidad Industrial de Santander. 24 records from R - Herbário do Museu Nacional. 35 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 4 records from HUESB - Herbário da Universidade Estadual do Sudoeste da Bahia. 1 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 24 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 3 records from Institute of Ecology and Evolutionary Biology, National Taiwan University. 97 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 1 records from Herbarium Amazonense. 1 records from Digital Florula - Palo Verde Biological Station. 2 records from SLUI - Herbário Rosa Mochel. 5 records from UB - Herbário da Universidade de Brasília. 1 records from PEUFR - Herbário Professor Vasconcelos Sobrinho. 1 records from Herbarium - Las Cruces Biological Station. 7 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 4 records from Allan Herbarium (CHR). 1 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 4 records from SysTax - Botanical Gardens. 1 records from SORO - Herbário do Centro de Ciências e Tecnologias para a Sustentabilidade. 20 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 14 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 4 records from Vascular Plant Herbarium, Oslo (O). 13 records from BUT Friesner Herbarium. 32 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 50 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 17 records from Geneva Herbarium – General Collection (G). 27 records from Instituto de Botánica Darwinion. 2 records from SJRP - Herbário de São José do Rio Preto. 36 records from Some Plant Specimens from PE Herbarium in China from 1900 to 1950. 1 records from CAS Botany (BOT). 8 records from CPAP - Herbário CPAP. 1 records from HEPH - Herbário Ezechias Paulo Heringer. 6 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 8 records from MOSS - Herbário Dárdano de Andrade Lima. 8 records from HRCB - Herbário Rioclarense. 1 records from PACA-AGP - Herbarium Anchieta. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences